Hadith #459 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
We were entrusted with the task of tending the camels. On my turn when I came back in the evening after grazing them in the pastures, I found Allah’s Messenger (ﷺ) stand and address the people. I heard these words of his: If any Muslim performs ablution well, then stands and prays two rak’ahs setting about them with his heart as well as his face, Paradise would be guaranteed to him. I said: What a fine thing is this! And a narrator who was before me said: The first was better than even thi
Grade: Sahih

Hadith #1765 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
When we were in Suffa, the Messenger of Allah (ﷺ) came out and said: Which of you would like to go out every morning to Buthan or al-‘Aqiq and bring two large she-camels without being guilty of sin or without severing the ties of kinship? We said: Messenger of Allah, we would like to do it. Upon this he said: Does not one of you go out in the morning to the mosque and teach or recite two verses from the Book of Allah. the Majestic and Glorious? That is better for him than two she-camels, and
Grade: Sahih

Hadith #1783 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
What wonderful verses have been sent down today. the like of which has never been seen! They are:” Say: I seek refuge with the Lord of the dawn,” and” Say: I seek refuge with the Lord of men.”
Grade: Sahih

Hadith #1784 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
The Messenger of Allah (ﷺ) said to me: There have been sent down to me verses the like of which had never been seen before. They are the Mu’awwadhatain.
Grade: Sahih

Hadith #1821 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
There were three times at which Allah’s Messenger (ﷺ) forbade us to pray, or bury our dead: When the sun begins to rise till it is fully up, when the sun is at its height at midday till it passes over the meridian, and when the sun draws near to setting till it sets.
Grade: Sahih

Hadith #3341 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
A believer is the brother of a believer, so it is not lawful for a believer to outbid his brother, and he should not propose an engagement when his brother has thus proposed until he gives it up.
Grade: Sahih

Hadith #3349 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
The most worthy condition which must be fulfilled is that which makes sexual intercourse lawful. In the narration transmitted by Ibn Muthanna (instead of the word” condition” ) it is” conditions”.
Grade: Sahih

Hadith #4121 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
My sister took a vow that she would walk bare foot to the house of Allah (Ka’ba). She asked me to inquire from Allah’s Messenger (ﷺ) about it. I sought his decision and he said: She should walk on foot and ride also.
Grade: Sahih

Hadith #4123 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
The expiation of the (breach of) a vow is the same as that of the (breach of an oath).
Grade: Sahih

Hadith #4385 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
We said to Allah’s Messenger (ﷺ): You send us out and we come to the people who do not give us hospitality, so what is your opinion? Thereupon Allah’s Messenger (ﷺ) said: If you come to the people who order for you what is befitting a guest, accept it; but if they do not. take from them what befits them to give to a guest.
Grade: Sahih

Hadith #4811 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
I heard the Messenger of Allah (ﷺ) say: Lands shall be thrown open to you and Allah will suffice you (against your enemies), but none of you should give up playing with his arrows.
Grade: Sahih

Hadith #4948 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
You sacrifice it.
Grade: Sahih

Hadith #5288 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
A silk go vn was presented to Allah’s Messenger (ﷺ) and he wore it and observed prayer in it and then returned and put it off so violently as if he despised it. He then said: It does not befit the Godfearing persons.
Grade: Sahih

Hadith #5527 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
Beware of getting, into the houses and meeting women (in seclusion). A person from the Ansar said: Allah’s Messenger, what about husband’s brother, whereupon he (ﷺ) said: Husband’s brother is like death.
Grade: Sahih

Hadith #5823 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
I shall be present there (at the Cistern) before you. I shall be your witness and, by Allah, I perceive as if I am seeing with my own eyes my Cistern at this very state and I have been given the keys of the treasures of the earth or the keys of the earth and, by Allah, I am not afraid concerning you that you would associate anything (with Allah after me), but I am afraid that you would be vying with one another (for the possession of) the treasures of the earth.
Grade: Sahih

Hadith #5824 - Sahih Muslim - Uqbah ibn Amir (Sahih Muslim)
Allah’s Messenger offered prayer over those who had fallen matyrs at Uhud. He then climbed the pulpit as if someone is saying good-bye to the living and the dead, and then said: I shall be there as your predecesor on the Cistern before you, and it is as wide as the distance between Aila and Juhfa (Aila is at the top of the gulf of ‘Aqaba). I am not afraid that you would associate anything with Allah after me, but I am afraid that you may be (allured) by the world and (vie) with one another (
Grade: Sahih